THE INFLUENCE OF SOCIODEMOGRAPHY OF THE POPULATION OF SUMENEP DISTRICT ON THE INTENSITY OF TOURIST VISITS - Elvi Kurniawati; Rasyid, Mohtar (JURNAL EKBIS, 2024)
This research aims to identify the sociodemographic characteristics of the Sumenep district population that influence the intensity of traveling to tourist attractions. In this research, the analysis method used is quantitative, data obtained from the Central Bureau of Statistics of the National Socio-Economic Survey of Sumenep District in 2021. The independent variables in this research are socio-demographic characteristics which include age, gender, married , education and occupation, while the dependent variable is the intensity of resident travel to tourist destinations. The analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the age variable has an insignificant effect, while other variables consisting of gender, marriage, education, and occupation have a significant effect on the intensity of tourist visits. The contribution of this research lies in the analysis focused on the sociodemographic characteristics of the Sumenep district population on the intensity of tourist visits using the National Socio-Economic Survey data.